ChemInform Abstract: Expeditious and Convenient Synthesis of Polycyclic Difluoroboron Complexes of 2‐Oxoindoline‐3‐carboxamides by Tandem Reaction. Issue 41 (22nd September 2016) - Mo, Shanyan; Xu, Chuangchuang; Xu, Jiaxi
Abstract: The boron trifluoride etherate serves as both a catalyst and reactant in the tandem reaction.